Pendidikan Kesehatan Health Belief Model (Hbm) terhadap Perilaku Diet Remaja - Sri Wahyuningsih; Susmiati Susmiati; Deswita Deswita (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of the Health Belief Model (HBM) health education on adolescent dietary behavior. The method used is quantitative with a quasi-experimental design with a pre-test and post-test design with a control group. The results showed that there was an increase in the average dietary behavior of adolescents after being given health education compared to before being given health education. The results of the analysis using statistical tests obtained values (p <0.05), so it can be concluded that there is a significant influence of the Health Belief Model (HBM) health education on adolescent dietary behavior. Conclusion: shows the effect of the Health Belief Model (HBM) health education on childish nutritional behavior. This can be proven according to the results of statistical tests with paired sample t-tests showing a value (p <0.05). Keywords: Health Belief Model (HBM), Health Education, Dietary Behavior, Adolescents